Optimization of Microgrid Battery Capacity using PSO with Considering Islanding Operation - Ayu Sintianingrum; Khairudin Khairudin; Lukmanul Hakim (Journal of Engineering and Scientific Research, 2020)
Electrical is used for various activities in all sectors. Rapid increase of electricity demand recently, makes it necessary to have an even more efficient method for generating electricity. Renewable energy and the microgrid provides an integrated and alternative solution for electricity generation. In microgrid systems, energy storage devices are one of important aspects. Batteries are one kind of the energy storage technologies widely used in power system and hence, their suitable capacity must be determined in order to develop an effective system installation. In this research, sizing optimization of battery capacity is modeled as a minimization of microgrid battery capacity using the Particle Swarm Optimization/PSO algorithm with considering islanding operation of the system for effective battery installation. Results show that optimal battery capacity can be obtained and the developed computational model gives satisfactory results for the system under study.   Keywords: Battery, microgrid, energy storage system, PSO algorithm